Water Formation under Silica Thin Films: Real‐Time Observation of a Chemical Reaction in a Physically Confined Space. Issue 28 (6th June 2018) - Prieto, Mauricio J.; Klemm, Hagen W.; Xiong, Feng; Gottlob, Daniel M.; Menzel, Dietrich; Schmidt, Thomas; Freund, Hans‐Joachim
Abstract: Using low‐energy electron microscopy and local photoelectron spectroscopy, water formation from adsorbed O and H2 on a Ru(0001) surface covered with a vitreous SiO2 bilayer (BL) was investigated and compared to the same reaction on bare Ru(0001). In both cases the reaction is characterized by moving reaction fronts. The reason for this might be related to the requirement of site release by O adatoms for further H2 ‐dissociative adsorption. Apparent activation energies ( E a a p p ) are found for the front motion of 0.59 eV without cover and 0.27 eV under cover. We suggest that the smaller activation energy but higher reaction temperature for the reaction on the SiO2 BL covered Ru(0001) surface is due to a change of the rate‐determining step. Other possible effects of the cover are discussed. Our results give the first values for E a a p p in confined space. Abstract : Under cover : Confinement of the water formation reaction beneath a silica thin film supported on Ru(0001) induces changes in the observed apparent activation energy ( E a a p p ) extracted from real‐time measurements. For instance, the E a a p p of the reaction under confinement is considerably lower (0.27 eV) than that without confinement (0.59 eV).